Net neutrality in the Netherlands: Dutch solution or Dutch disease? - Roslyn Layton (International Telecommunications Society (ITS), 2013)
The law of net neutrality has been in effect in the Netherlands since January 1, 2013, after having been passed on June 5, 2011 by the Lower House of the Dutch Parliament and then ratified by the Upper House a year later. This paper investigates the policy, its process, and its impact. It offers a review of the background of the problem; the design and conceptualization of the policy response, the implementation of the policy, the impact of the policy and an assessment of the policy. It also provides a discussion of the market for over the top (OTT) technology services and its role in the market. Interviews with key stakeholders were conducted to provide further insight. A financial analysis is also offered to help inform the issue. As net neutrality is on the agenda of regulators worldwide, such an analysis can be helpful to policymakers. Other countries looking to implement such a rule might learn from the Dutch example.
Keywords: 330